The Relationship Between the Gamification Approach in Training Development and Job Performance in Service Sector - Zaid, Alea; Shazaitul Azreen (Research in Management of Technology and Business, 2025)
The rapid advancement of technology has transformed how industries approach employee training and development. In Malaysia’s service sector, which plays a crucial role in driving the nation’s economy, traditional training methods often struggle to keep up with the growing need for efficiency, innovation, and precision. To address these challenges, gamification using game design elements in non-gaming settings has emerged as a promising way to make training more engaging and effective. Using a quantitative research approach, surveys were distributed to service-related businesses employees. The data collected was then analysed to assess how gamified training affects skill retention, productivity, and job satisfaction. The findings suggest that integrating gamification into training programs not only improves employee engagement but also leads to better learning outcomes and overall job performance. However, challenges such as implementation costs and adaptability were noted, indicating that while gamification has great potential, a well-planned approach is necessary for its success. This study provides practical recommendations for organisations looking to improve their training strategies by projecting the spotlight on the impact of gamified learning. The insights gained can help businesses create more effective training programs, boost workforce motivation, and maintain a competitive edge in Malaysia’s growing service sector.